Bulk Iodoapatite Ceramic Densified by Spark Plasma Sintering with Exceptional Thermal Stability. Issue 8 (16th July 2014) - Yao, Tiankai; Lu, Fengyuan; Sun, Hongtao; Wang, Jianwei; Ewing, Rodney C.; Lian, Jie; Ballarini, R.
<x xml:space="preserve">Abstract</x> Iodoapatite powder prepared by high‐energy ball milling is densified by Spark Plasma Sintering to ~96% theoretical density. X‐ray Diffraction and First‐principle Calculation indicates the sintered phase is iodine‐deficient apatite with chemical composition of Pb9.85(VO4)6I1.7 and iodine confinement over 8 wt%. Thermogravimetric analysis shows the bulk iodoapatite displays exceptionally stability without iodine release until 670°C. The greatly improved iodine confinement can be attributed to the dense matrix upon rapid consolidation from highly activated powders by mechanical attrition.